A DWT-SVD based multiple watermarking scheme for image based data security. Issue 1 (2nd January 2018) - Singh, Ranjeet Kumar; Shaw, Dillip Kumar; Jha, Sudhanshu Kumar; Kumar, Manish
Abstract: In this paper a novel image based data security and authentication based, image watermarking scheme that combines the discrete wavelet transform (DWT) and Singular value decomposition (SVD) is proposed. This paper explains a dual watermarking scheme with different algorithm. At first original image is divided into its appropriate levels by using DWT, and convert LL sub-band to its red, green and blue component, and the obtained colour component of image is divided into non-overlapping blocks, final apply SVD on each block to obtained the singular value for watermarking. The second scheme chose HH sub-band of original image and converts its own red, green, blue component, and then apply SVD to each colour component to obtain the singular value for watermarking. We take two watermark images one is Logo image and other is Quick Response Code (QR Code) for experiment. Results obtained from the experiment reflect the efficiency of the proposed scheme.